The Maqāṣidi Thought of AL-Imam AL-Sarakhsi - Mousa, Moayad Hamdan Mahmoud (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: The study aims to highlight the features of Imam Al-Sarakhsi’s maqasid (objectives) thought by clarifying the most important maqasid-based tools he used to uncover the objectives of Islamic law (shari’ah). It also explores his conceptualization of general, specific, and partial objectives of legislation, as well as the impact of Imam Al-Sarakhsi’s thought on the science of maqasid. Methods: The study adopted the inductive, analytical, and deductive methodologies. It surveyed the three major works of Imam Al-Sarakhsi: Al-Mabsut, Sharh Al-Siyar Al-Kabir, and Usul Al-Sarakhsi, to extract matters related to the objectives of shari’ah. The analysis involved examining Al-Sarakhsi’s statements and his jurisprudential reasoning to deduce the most prominent features of his maqasid-oriented thought. Results: Imam Al-Sarakhsi demonstrated a maqasid-oriented approach in his works, dictated from memory while imprisoned. He relied on istihsan (juridical preference) and qawa’id rasm al-mufti (rules for issuing fatwas), key Hanafi tools for maqasid application. His thought centered on three legislative objectives: reverence for Allah, preservation of human life, and preventing corruption. He also focused on defining general and specific objectives within various jurisprudential categories, showcasing his meticulous legal reasoning. Conclusions: Imam Al-Sarakhsi’s pioneering contributions to some general concepts of the science of maqasid, along with the profound significance of his works in addressing maqasid from a practical perspective, were underscored. The study recommends conducting specialized research to present the objectives of shari’ah in a systematic manner, as articulated by early jurists.